Phonological Processing, Family Support, and Academic Self-Concept as Predictors of Early Reading - Carson, Linda; Kirby, John; Hutchinson, Nancy (Canadian Journal of Education/Revue canadienne de l’éducation, 2000)
We investigated factors related to early reading achievement: phonological pro- cessing, family support, academic self-concept. The subjects were 72 children in Grade 1. Predictors were measured in October. In May, the children’s reading achievement was measured using subtests of the Woodcock Reading Mastery Tests – Revised and teacher appraisals. The predictors accounted for 47%–54% of the variance in the various reading scores, but only the phonological processing measures contributed a statistically significant amount. These results support the importance of phonological processing in early reading, and raise questions about the predictive utility of family support and self-concept measures. L’article traite des facteurs reliés à la maîtrise de la lecture précoce : traitement phonologique, soutien familial et estime de soi. Les sujets étaient 72 enfants de pre- mière année. Les prédicteurs ont été mesurés en octobre. En mai, la maîtrise de la lecture a été mesurée à l’aide de sous-tests du test révisé de maîtrise de la lecture de Woodcock et des évaluations des enseignants. Les prédicteurs expliquaient l’écart dans les résultats obtenus dans une proportion de 47 à 54 %. Seules les mesures ayant trait au traitement phonologique ont contribué à des résultats statistiquement significatifs.